Sulla bellezza delle donne: Un percorso PCTO tra chimica, storia ed economia solidale - Capuano, Fabio (Chimica nella Scuola, 2022)
A class of a technical institute for chemistry developed a PCTO path focused on the realization of cosmetics inspired by the recipes of Trotula De Ruggiero, a prominent exponent of the ancient “Schola Medica Salernitana”. These recipes were revisited by highlighting, from a chemical perspective, the ingredients that, in the modern cosmetic science, are still considered valid, and those that have been rejected. Starting from a protocol between MIUR and Confcooperative, and with the training support of the “Stalker” Social Cooperative of Eboli (SA), the class made up a Scholastic Cooperative Association, implementing in a business simulation the management of activities through the practical application of the cooperative principles. The present contribution describes the different aspects of this educational path that seeks a strong motivational impulse to learning in the interaction between chemistry, history and solidarity economy.